Effects of Water Solutions on Extracting Green Tea Leaves - Wen-Ying Huang; Yu-Ru Lin; Ruei-Fen Ho; Ho-Yen Liu; Yung-Sheng Lin (The Scientific World Journal)
This study investigates the effects of water solutions on the antioxidant content of green tea leaf extracts. Green teas prepared with tap water and distilled water were compared with respect to four antioxidant assays: total phenol content, reducing power, DMPD assay, and trolox equivalent antioxidant capacity assay. The results indicate that green tea prepared with distilled water exhibits higher antioxidant activity than that made with tap water. The high performance liquid chromatography showed that major constituents of green tea were found in higher concentrations in tea made with distilled water than in that made with tap water. This could be due to less calcium fixation in leaves and small water clusters. Water solutions composed of less mineralisation are more effective in promoting the quality of green tea leaf extracts.